Nutrigenomics and direct-to-consumer nutrigenomics services in light of Βioethics - Ανεστίδου (Anastasia Ioanna Anestidou) Αναστασία Ιωάννα; Σπυροπούλου (Tatiani Spyropoulou) Τατιανή; Κουρκουτίδου (Maria Kourkoutidou) Μαρία; Χατζοβούλου (Evangelia Chatzovoulou) Ευαγγελία; Βογιατζάκης (Christos Vogiatzakis) Χρήστος; Κοσσιαρά (Chryssoula Kossiara) Χρυσούλα; Ξηρογιάννη (Sotiria Xirogianni) Σωτηρία; Κατσίλα (Theodora Katsila) Θεοδώρα; Πατρινός (Giorgos Patrinos) Γιώργος (Bioethica, 2017)
Nutrigenomics, an emerging genomics field, aims to explore the interactions between nutrition and genes. Notably, nutrigenomics information and applications seem to be directly accessible to the public, partly due to advertising and direct-to-consumer online sales of nutrigenomics-related products and services. Nowadays, consumers have direct access to their genetic information. Access, however, does not guarantee interpretation and utility. This article, discusses the ethical and regulatory aspects of direct-to-consumer genetic services, focusing on nutrigenomic tests and the means they are promoted to the general public.